Country drug report - Europäische Kommission - Beobachtungsstelle für Drogen und Drogensucht (2009)
"Country Drug Reports provide a top-level overview of the drug phenomenon in European countries, covering topics such as drug supply, drug use and public health problems as well as drug policy and responses. Each Country Drug Report focuses on a single country (28 EU Member States as well as Norway and Turkey, with which the EMCDDA has a special agreement) and is structured thematically. Individual sections are designed so that they may be read in isolation. Country Drug Reports are designed for online viewing but simple PDFs exist for each country. Country Drug Reports are created in collaboration with the Reitox national focal point for the country in question. The statistical data reported relate to 2016 (or most recent year) unless stated otherwise. Country Drug Reports are published anually each year alongside the European Drug Report".